Analysis of Social Movements by Athletes : Study on Black Equality and Justice Campaign by Lebron James - Muhammad Fadzryl Adzmy; Ashadi Ashar (Jurnal Partisipatoris, 2025)
This study aims to examine the social movement advocating for civil rights and combating racism that was instigated by a renowned basketball athlete, LeBron James, within the United States. The study of social movements, which are collective behaviours initiated by grassroots groups in pursuit of their objectives, has been of significant scholarly interest since the early 20th century. Typically, scholarly investigations pertaining to social movements prioritise the examination of contextual factors around the issue at hand, as well as the individual reasons that drive the participants' engagement. In the present-day context, the occurrence of social movements is expanding and exhibiting inherent intricacy, encompassing a diverse range of concerns and participants. This study aims to conduct an in-depth examination of the social movement spearheaded by LeBron James, a renowned basketball athlete in the United States. James has demonstrated a sustained commitment to advocating for the civil rights of black individuals. The existing body of literature reveals a dearth of research on social movements initiated or executed by athletes. Consequently, doing this study is of significant scholarly importance. The results indicate that the initiation of this movement by a prominent athlete is intrinsically linked to the sense of collective identification shared between the athlete and the marginalised groups whose rights are being advocated for. Furthermore, the emergence of this movement can be attributed to other elements, notably the cultivation of unity and dedication among the individuals involved in the movement spearheaded by LeBron James.